(3GdehGbas - (3YHO GdbGOQ Hf eMjj GdOjf Hf eUWaj GdMSfj GdLRGFQj,J (B1300 (3g` s
(3ChdgG (B:s
(3bGd SjOfG hGSJGPfG GdMeO ddg MeOkG jhGai fYeg gPg faKGJ QhMjI hGdbGAGJ SHhMjI bGd Gddg JYGdi (B: ( (3dbO cGf dce ai QShd Gddg EShI MSfI (B) s
(3BNQgG (B:s
(3aGdMPQ GdMPQ ef GdNhV ai GdfHhI hGdCfHjGA eWdbG aGddg jYUefG hGjGce ef GdRdd ai Gdbhd hGdYed hHYO cJGHJi dgPG Gdehba Hbdjd hQO Ydi ai GdhGbYI bhdg (B: ( (3hLhg jeFP fGYeI dSYjgG QGVjI (B) (3Je GdLRA GdChd ef GdehGba s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B45s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG s
Keywords: (3GdbQGAGJ hGdJLhjOs